Il giardino riflesso L'erbario di Luigi Meneghello - Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2015)
In Luigi Meneghello's work, the representation of the plant world refers to a subtext of images and symbols: a network of botanical isotopies which transforms into a system while allowing for an alternative and unprecedented reading. From the pages of Libera nos a malo (1963), up to the 'posthumous letters' of L'appendistato (2012), what the author calls «inframondo verdastro» becomes the starting point for the restoration of a literary biosphere, one which is constantly crossed by a double movement: intertextual memory and continuous interaction between Italian, English and the dialect from Vicenza (Italy). Meneghello's 'reflected garden' thus reveals itself in all its semantic value, and sheds light on a theme of surprisingly great complexity, and also a subject of particular interest for literary ecocriticism.